2018
DOI: 10.1177/1179069518809057
|View full text |Cite
|
Sign up to set email alerts
|

Context-Sensitive Computational Mechanisms of Decision Making

Abstract: Real-world information is primarily sensory in nature, and understandably people attach value to the sensory information to prepare for appropriate behavioral responses. This review presents research from value-based, perceptual, and social decision-making domains, so far studied using isolated paradigms and their corresponding computational models. For example, in perceptual decision making, the sensory evidence accumulation rather than value computation becomes central to choice behavior. Furthermore, we ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Even though some previous studies have suggested that DLPFC activity may reflect value-based evidence integration , Sokol-Hessner et al 2012, it is hard to directly compare the implicated neural processes to those underlying perceptual choices, due to major differences in the stimuli and experimental approaches classically used in each domain (Balleine 2007, Gold and Shadlen 2007, Krawczyk 2002. While there are good theoretical reasons to believe that common mechanisms may underlie both perceptual and value-based choices (Chawla andMiyapuram 2018, Summerfield andTsetsos 2012), the number of studies directly comparing the neural mechanisms between both choice domains is surprisingly limited. The few existing studies have all used correlational neuroimaging techniques (Grueschow et al 2015, Polania et al 2014, and no study to date has used causal brain-stimulation techniques in combination with neuroimaging to directly compare the neuro-computational contributions of the SFS to both types of choice.…”
Section: Introductionmentioning
confidence: 99%
“…Even though some previous studies have suggested that DLPFC activity may reflect value-based evidence integration , Sokol-Hessner et al 2012, it is hard to directly compare the implicated neural processes to those underlying perceptual choices, due to major differences in the stimuli and experimental approaches classically used in each domain (Balleine 2007, Gold and Shadlen 2007, Krawczyk 2002. While there are good theoretical reasons to believe that common mechanisms may underlie both perceptual and value-based choices (Chawla andMiyapuram 2018, Summerfield andTsetsos 2012), the number of studies directly comparing the neural mechanisms between both choice domains is surprisingly limited. The few existing studies have all used correlational neuroimaging techniques (Grueschow et al 2015, Polania et al 2014, and no study to date has used causal brain-stimulation techniques in combination with neuroimaging to directly compare the neuro-computational contributions of the SFS to both types of choice.…”
Section: Introductionmentioning
confidence: 99%